Kajian Struktur dan Komunikasi Organisasi Universitas Padjadjaran (Unpad) - Rangga Saptya Mohamad Permana; Aceng Abdullah (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2018)
In 2016, Rector of Universitas Padjadjaran (Unpad) issued a regulation on the organization and working procedures of Unpad managers. In the framework of university management in a formal context, the academic community of Unpad involves organizational communication. Organizational communication is used primarily within the structural scope of university or faculty managers. The messages dissemination from leaders to subordinates, inputs and suggestions from subordinates to leaders, and exchange of messages between officials is done through organizational communication. The research method used in this study is a descriptive-qualitative method. Using documentation method, the author seeks to explain and focus on how the structure and communication of management organization in Unpad. The results of the study indicate that Unpad's organizational structure is included in the organizational structure carrying out organizational levels between two and three levels, called flat top organization structure. Based on the organizational structure chart, Unpad adheres to a form of centralization in its organizational structure. While organizational communication that can be applied to Unpad's communication structure includes internal communication within the organization and external communication to/from outside the organization which are based on Unpad's organizational culture, RESPECT.